Involvement of monoaminergic system in the antidepressant-like effect of aqueous extract of Channa striatus in mice - Saleem, A. M.; Baharuldin, Mohamad Taufik Hidayat; Mat Jais, Abdul Manan; Fakurazi, Sharida; Mohd Moklas, Mohamad Aris; Sulaiman, Mohd Roslan; Amom, Zulkhairi; Basir, Rusliza (Verduci Editore, 2013)
BACKGROUND: In our previous study, the aqueous extract of Channa striatus (family: Channidae) fillet (AECSF) showed an antidepressant-like effect in mice. However, the mechanism of the antidepressant-like effect is unknown. AIM: The objective of this study was to explore the involvement of monoamines in the antidepressant-like effect of AECSF in mice. MATERIALS AND METHODS: AECSF was prepared by steaming the fillets of C. striatus. The male ICR mice were pretreated with various monoaminergic antagonists viz., p-chlorophenylalanine (100 mg/kg, i.p.), prazosin (1 mg/kg, i.p.) and yohimbine (1 mg/kg, i.p.), SCH23390 (0.05 mg/kg, s.c.) and sulpiride (50 mg/kg, i.p.) followed by treatment with AECSF and tested in tail suspension test (TST). Two-way ANOVA with Tukey test were used at p < 0.05 for significance. RESULTS: The pretreatments with p-chlorophenylalanine, prazosin and yohimbine, but not with SCH23390 and sulpiride, were able to reverse the antidepressant-like effect of AECSF in TST. CONCLUSIONS: The antidepressant-like effect of AECSF may be mediated through the serotonergic and noradrenergic systems and not through the dopaminergic system.